Particles And The Universe - Proceedings Of The Eighteenth Lake Louise Winter Institute. - Astbury, A. (World Scientific, 2004)
The Lake Louise Winter Institute is held annually to explore recent trends in physics. Pedagogical and review lectures are presented by invited experts. A topical workshop is held in conjunction with the Institute, with contributed presentations by participants.